2020
DOI: 10.1155/2020/7264171
|View full text |Cite
|
Sign up to set email alerts
|

Adult Literacy and Skill Acquisition Programmes as Correlates of Women Empowerment and Self-Reliance in The Gambia

Abstract: Self-reliance and empowerment for women have been at the centre of the agitations for gender balance in Africa. Women are largely marginalised, and obvious gender disparity exists in school enrolment and completion rates in most African countries, particularly in e Gambia. Efforts to address this shortfall led to the adoption of adult literacy and skill acquisition programmes to build the capacity of women and out-of-school adults. Training contents were developed and centres set up across the six educational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…As discussed earlier, mastery of foundational skills may help students keep up with the curriculum, and as a result, stay in school. Staying in school longer and specifically learning while in school are associated with such positive benefits as reduction in fertility rates and child mortality, improvement in female empowerment, and financial behaviours index (Olagbaju, 2020;Mensch et al, 2019;Kaffenberger and Pritchett, 2020; Figure 4). Studies have also suggested linkages between foundational skills and general problem solving skills (Lucangeli et al, 1998;Pugalee, 1999).…”
Section: Foundational Skills Are Associated With Societal Economic Be...mentioning
confidence: 99%
“…As discussed earlier, mastery of foundational skills may help students keep up with the curriculum, and as a result, stay in school. Staying in school longer and specifically learning while in school are associated with such positive benefits as reduction in fertility rates and child mortality, improvement in female empowerment, and financial behaviours index (Olagbaju, 2020;Mensch et al, 2019;Kaffenberger and Pritchett, 2020; Figure 4). Studies have also suggested linkages between foundational skills and general problem solving skills (Lucangeli et al, 1998;Pugalee, 1999).…”
Section: Foundational Skills Are Associated With Societal Economic Be...mentioning
confidence: 99%
“…Empowerment has become a common concept in development and feminist literature, within which several definitions of empowerment exist. Ojediran and Anderson (2020) suggest that empowerment pertains to five dimensions: social, economic, educational, political and psychological (Ojediran & Anderson, 2020). For this study, I build on feminist perspectives of WE and focus on human agency and self-efficacy, centred on the notion of 'inner transformation' to exercise choice (Adjei, 2015).…”
Section: Key Terms Women Empowerment (We)mentioning
confidence: 99%
“…For this study, I build on feminist perspectives of WE and focus on human agency and self-efficacy, centred on the notion of 'inner transformation' to exercise choice (Adjei, 2015). As such, I define WE as building a woman's capacity to be able to make strategic life choices, and developing their agency to act effectively within current power structures and systems (Ojediran & Anderson, 2020).…”
Section: Key Terms Women Empowerment (We)mentioning
confidence: 99%
See 1 more Smart Citation